Size, shape, and lateral correlation of highly uniform, mesoscopic, self-assembled domains of fluorocarbon-hydrocarbon diblocks at the air/water interface: a GISAXS study - Veschgini, Mariam; Abuillan, Wasim; Inoue, Shigeto; Mielke, Salomé; Tanaka, Motomu (ChemPhysChem, 2017)
The shape and size of self-assembled mesoscopic surface domains of fluorocarbon-hydrocarbon (FnHm) diblocks and the lateral correlation between these domains were quantitatively determined from grazing incidence small-angle X-ray scattering (GISAXS). The full calculation of structure and form factors unravels the influence of fluorocarbon and hydrocarbon block lengths on the diameter and height of the domains, and provides the inter-domain correlation length. The diameter of the domains, as determined from the form factor analysis, exhibits a monotonic increase in response to the systematic lengthening of each block, which can be attributed to the increase in van der Waals attraction between molecules. The pair correlation function in real space calculated from the structure factor implies that the inter-domain correlation can reach a distance that is over 25 times larger than the domain's size. The full calculation of the GISAXS signals introduced here opens a potential towards the hierarchical design of mesoscale domains of self-assembled small organic molecules, covering several orders of magnitude in space.